Association of polycystic ovary syndrome or anovulatory infertility with offspring psychiatric and mild neurodevelopmental disorders: a Finnish population-based cohort study - Xinxia Chen; Linghua Kong; Terhi T Piltonen; Mika Gissler; Catharina Lavebratt (Oxford University Press, 2022)
STUDY QUESTION
Is maternal polycystic ovary syndrome (PCOS) associated with increased risks for a broad spectrum of psychiatric and mild neurodevelopmental disorders in offspring?
SUMMARY ANSWER
Maternal PCOS and/or anovulatory infertility is independently, and jointly with maternal obesity, perinatal problems, cesarean delivery and gestational diabetes, associated with increased risks in offspring for almost all groups of psychiatric and mild neurodevelopmental disorders with onset in childhood or adolescence.
WHAT IS KNOWN ALREADY
Maternal PCOS was previously associated with autism spectrum disorder, attention-deficit/hyperactivity disorders and possibly developmental delay in offspring. Few studies have investigated the association between maternal PCOS and other psychiatric and neurodevelopmental disorders in offspring.
STUDY DESIGN, SIZE, DURATION
This was a population-based cohort study in Finland including all live births between 1996 and 2014 (n = 1 105 997). After excluding births to mothers with symptoms similar to PCOS, a total of 1 097 753 births by 590 939 mothers remained. Children were followed up until 31 December 2018, i.e. up to the age of 22 years.
PARTICIPANTS/MATERIALS, SETTING, METHODS
National registries were used to link data of the included births and their mothers. Data from 24 682 (2.2%) children born to mothers with PCOS were compared with 1 073 071 (97.8%) children born to mothers without PCOS. Cox proportional hazards modeling was used to evaluate the hazard ratio (HR) and 95% CI for the risk of neuropsychiatric disorders in relation to maternal PCOS. Stratified analyses were performed to test the independent role of PCOS and the joint effects of PCOS with maternal obesity, perinatal problems, cesarean delivery, gestational diabetes and use of fertility treatment. The analysis was adjusted for maternal age, country of birth, marriage status at birth, smoking, parity, psychiatric disorders, prescription of psychotropic N05/N06 during pregnancy and systemic inflammatory diseases when applicable.
MAIN RESULTS AND THE ROLE OF CHANCE
A total of 105 409 (9.8%) children were diagnosed with a neurodevelopmental or psychiatric disorder. Firstly, maternal PCOS was associated with any psychiatric diagnosis (HR 1.32; 95% CI 1.27–1.38) in offspring. Particularly, the risk was increased for sleeping disorders (HR 1.46; 95% CI 1.27–1.67), attention-deficit/hyperactivity disorders and conduct disorders (HR 1.42; 95% CI 1.33–1.52), tic disorders (HR 1.42; 95% CI 1.21–1.68), intellectual disabilities (HR 1.41; 95% CI 1.24–1.60), autism spectrum disorder (HR 1.40; 95% CI 1.26–1.57), specific developmental disorders (HR 1.37; 95% CI 1.30–1.43), eating disorders (HR 1.36; 95% CI 1.15–1.61), anxiety disorders (HR 1.33; 95% CI 1.26–1.41), mood disorders (HR 1.27; 95% CI 1.18–1.35) and other behavioral and emotional disorders (ICD-10 F98, HR 1.49; 95% CI 1.39–1.59). In short, there was no significant difference between sexes. The results were robust when restricting the analyses to the first-born children or births to mothers without psychiatric diagnosis or purchase of psychotropic medication. Secondly, stratified analysis according to maternal BMI showed that the risk of any neuropsychiatric disorder was increased in offspring to normal-weight mothers with PCOS (HR 1.20; 95% CI 1.09–1.32), and markedly higher in those to severely obese mothers with PCOS (HR 2.11; 95% CI 1.76–2.53) compared to offspring to normal-weight mothers without PCOS. When excluding perinatal problems, mothers with PCOS were still associated with increased risks of any neuropsychiatric disorders in offspring (HR 1.28; 95% CI 1.22–1.34) compared to mothers without PCOS. However, an additional increase was observed for PCOS in combination with perinatal problems (HR 1.99; 95% CI 1.84–2.16). Likewise, excluding cases with maternal gestational diabetes (HR 1.30; 95% CI 1.25–1.36), cesarean delivery (HR 1.29; 95% CI 1.23–1.35) or fertility treatment (HR 1.31; 95% CI 1.25–1.36) did not eliminate the associations.
LIMITATIONS, REASONS FOR CAUTION
The register-based prevalence of PCOS was lower than previously reported, suggesting that this study may capture the most severe cases. To combine anovulatory infertility with PCOS diagnosis as PCOS exposure might introduce diagnostic bias. It was not feasible to distinguish between subtypes of PCOS. Furthermore, familial factors might confound the association between maternal PCOS and neuropsychiatric disorders in offspring. Maternal BMI was available for birth cohort 2004–2014 only and there was no information on gestational weight gain.
WIDER IMPLICATIONS OF THE FINDINGS
This study provides further evidence that maternal PCOS and/or anovulatory infertility, independently and jointly with maternal obesity, perinatal problems, gestational diabetes and cesarean delivery, implies a broad range of adverse effects on offspring neurodevelopment. These findings may potentially help in counseling and managing pregnancies.